The advertisement call of Dendropsophus novaisi (Bokermann, 1968) (Anura: Hylidae: Dendropsophinae) - Protázio, Arielson Dos Santos; Protázio, Airan Dos Santos; Conceição, Lennise Costa; Braga, Hugo Santos Neri; Santos, Uilton Góes Dos; Ribeiro, André Caetité; Souza, Isana Carla Amorim (Zootaxa, 2017)
Dendropsophus novaisi (Bokermann,1968) was described from Maracás Municipality, State of Bahia, Brazil. Since its description, the species has been reported for one additional location in the State of Minas Gerais (Pedra Azul - Gomes & Peixoto 1996; Peixoto & Pimenta 2004) and five additional locations in Bahia (Boa Nova, Jequié, Jeremoabo, Camacan and Pau Brasil - Gomes & Peixoto 1996; Santos-Silva et al. 2012; Silva et al. 2013; Dias et al. 2014). However, information is still scarce about reproductive, ecological and acoustic characteristics of this treefrog. Here, we describe the advertisement call of D. novaisi and provide the geographic record of a new population.